A organização do trabalho e a saúde dos gerentes bancários em uma instituição no Estado do Espírito Santo - Bubach, Rosana (2006)
It rescues the transformations in the present work relationships, most of them came from productive restructuring process, sinking their workers, putting the work as if it was weak and promote the unemployment. It emphasizes the national bank system that suffers with changes such as client segmentation, diversification of products which were made specially to be sold and incorporation of new technologies. This contributes to intensify the work process, to make work-time more flexible and a considerable salary reduction, among other problems, it also demands a more qualified, polyvalent worker. Thus, this study has as a main goal to make an analysis between the bank work organization and their workers health, mainly talking about the relationship of managers with their front desk workers in a specific estate bank in EspÃrito Santo. It focus on the manager workers because of their behavior in front of the too long hours of work; the excessive number of tasks to be developed like the customer service and the achievement of goals; the responsibility for the operations and also in the mobility/instability of the personality of each person, that are experienced by the fact of staying in trustable function. It is related to a field, qualitative and exploratory research. It knows the managerâ€™s worker related to their front desk people, by semi-structured interviews with five workers and returns to talk with one of them considering the necessity of further clarification. The main questions intend to cover topics here are: what is it like to be a manager; the relation among the written and real work, how to work and the life in a general manner, looking for an articulation between the managerâ€™s activities and his or her health, i.e., his or her abilities to overcome the moment situation and to set new rules. The discussion and analysis of the collected data are given by the contributions of the Workerâ€™s Health Field, considering the meaning of health purposed by Canguilhemâ€™s and the concepts of the ergologic approach, understanding that each work situation is unique and that is necessary to know the workers experiencesâ€™. It emphasizes, from these actors, that to be a manager has to take into consideration the intensive mobilization and the completely engagement in front of the main imposed assignment: to achieve the goals. By this reason, managers are controlled and feel themselves threatened, resulting in fear and obstacles to express the sufferings and restandardization. On the other hand, managers also resist to the domination as well as they search for a sense in an everyday routine with many lacks confrontations, negotiations and constant (re)inventions.